Pengaruh Pemanfaatan Limbah Kulit Kerang Bambu Sebagai Pengganti Sebagian Semen Terhadap Kuat Tekan Beton dengan Penggunaan Agregat Kasar Madura - Irwanto, Taurina Jemmy; Irmawan, Agus (Universitas Dr. Soetomo, 2021)
Concrete is a mixture of Portland cement, fine aggregate, coarse aggregate and water, the author tries to use local Madura crushed stone and bamboo shells as a partial substitute for cement to determine whether the effect of utilizing local waste and materials on the planned compressive strength of concrete. In addition to the use of local materials, it is used shellfish waste which is expected to be able to provide the latest innovations in the world of construction in the future. In this test, concrete is planned in the form of a cube of size 15x15x15 cm, and tested at the age of 7 days and 28 days for each variation of the mixture, the research was carried out using several variations of the concrete mixture, namely, 0%, 2%, 4% and 6% replacement of cement with shells. bamboo shells, where later the 0% variation will be the benchmark for each variation. From the results of testing the chemical content of bamboo clam shells, it was found that the content of lime (CaO) was 98.23%. The results of the compressive test for each variation resulted in an increase in compressive strength from each variation. The greatest increase in compressive strength is at 6% variation with the resulting compressive strength of 21.94 MPa.